2014
DOI: 10.4236/ojas.2014.45031
|View full text |Cite
|
Sign up to set email alerts
|

Rearing Velocity Impacts on Landlocked Fall Chinook Salmon (<i>Oncorhynchus tshawytscha</i>) Growth, Condition, and Survival

Abstract: Juvenile landlocked Chinook salmon (Oncorhynchus tshawytscha) (mean ± SD initial weight 2.6 ± 0.7 g, fork length 6.3 ± 0.5) were reared in three different water velocities [0.5, 1.5 and 3.0 body length/s (BL/s)] for four weeks to determine possible effects of water velocity on growth, condition, and survival. Fish were sampled for weight, fork length, condition factor, hepatosomatic index (HSI), viscerosomatic index (VSI), and fin erosion after four weeks of feeding to satiation. At the end of the feeding tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Similar to the results of this study, where Rainbow Trout growth was negatively affected by the 2.75 BL/s rearing velocity, Parker and Barnes (2014) observed reduced growth and poorer feed conversion in Chinook Salmon O.tshawytscha reared in circular tank velocities of 3.0 BL/s versus in lower velocities of 0.5 and 1.5 BL/s, and Kiessling et al (1994) reported a decrease in food conversion with increases in swimming speed. Leon (1986) also observed similar growth decreases and feed conversion increases in Brook Trout Salvelinus fontinalis reared at higher velocities.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the results of this study, where Rainbow Trout growth was negatively affected by the 2.75 BL/s rearing velocity, Parker and Barnes (2014) observed reduced growth and poorer feed conversion in Chinook Salmon O.tshawytscha reared in circular tank velocities of 3.0 BL/s versus in lower velocities of 0.5 and 1.5 BL/s, and Kiessling et al (1994) reported a decrease in food conversion with increases in swimming speed. Leon (1986) also observed similar growth decreases and feed conversion increases in Brook Trout Salvelinus fontinalis reared at higher velocities.…”
Section: Discussionsupporting
confidence: 90%
“…It would also explain the more pronounced effects of rods at higher velocities observed by Kientz and Barnes [7]. While some water velocity has been shown to improve fish growth and feeding efficiency [8,9], higher velocities can lead to decreased rearing performance [10,11] due to excessive energy requirements [2].…”
Section: Discussionmentioning
confidence: 80%
“…Oxygen consumption of Sockeye Salmon O. nerka and Chinook Salmon increases as swimming speed increases (Brett and Glass 1973;Gallaugher et al 2001), and Chinook Salmon food utilization efficiency decreases with increased swimming speeds (Kiessling et al 1994). Additionally, Parker and Barnes (2014) demonstrated that Chinook Salmon had reduced growth and poorer feed conversion when forced to swim 3.0 BL/s compared with 0.5 and 1.5 BL/s. The poorer growth and feed conversion of the trout fed restricted rations swimming at 1.5 and 3.0 BL/s in our study is probably due to energy being allocated toward swimming, thereby reducing the net energy available for growth and consequently increasing feed conversion ratios.…”
Section: Discussionmentioning
confidence: 99%